A Review on Techniques Used for Solving the Economic Load Dispatch Problems: Categorization, Advantages, and Limitations - Sabo Aliyu; Sadiq N. Buba; Kabir Muhammed; Samuel Ephraim Kalau; Daramola P. Olaniyi; Abdulmajid Muhammed Na'inna; Veerapandiyan Veerasamy (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2025)
The increasing global demand for electric power presents significant challenges for power utilities, as they must balance the need for reliable and sustainable power generation with the goal to minimize generation costs. This challenge has led to studying Economic Load Dispatch (ELD), which aims to optimize power generation at minimal fuel costs.  This paper presents a comprehensive review of several primary techniques used in solving ELD problems, including traditional methods such as the Lambda Iteration, Gradient, and Newton-Raphson techniques, as well as modern optimization methods like Genetic Algorithm (GA), Simulated Annealing (SA), Particle Swarm Optimization (PSO), Artificial Bee Colony (ABC), Sine Cosine Algorithm (SCA), and Gravitational Search Algorithm (GSA). The paper also provides a comparative analysis using tables and chart in section three outlining the advantages, disadvantages, and limitations of each technique discussed in section two. Additionally, this review examines the applications of these techniques on IEEE test systems in various studies, highlighting their effectiveness on practical utility making it easier for researchers to make a choice in selecting a technique for their ELD problem.